Pharmaceutical strategic purchasing requirements in Iran: Price interventions and the related effective factors - Peivand Bastani; Rasoul Dinarvand; Mahnaz SamadBeik; Kimia Pourmohammadi (Wolters Kluwer Medknow Publications, 2016)
Objective: Pharmaceutical access for the poor is an essential factor in developing countries that can be improved through strategic purchasing. This study was conducted to identify the elements affecting price in order to enable insurance organizations to put strategic purchasing into practice. Methods: This was a qualitative study conducted through content analysis with an inductive approach applying a five-stage framework analysis (familiarization, identifying a thematic framework, indexing, mapping, and interpretation). Data analysis was started right after transcribing each interview applying ATLAS.ti. Data were saturated after 32 semi-structured interviews by experts. These key informants were selected purposefully and through snowball sampling. Findings: Findings showed that there are four main themes as Pharmaceutical Strategic Purchasing Requirements in Iran as follows essential and structural factors, international factors, economical factors, and legal factors. Moreover, totally 14 related sub-themes were extracted in this area as the main effective variables. Conclusion: It seems that paying adequate attention to the four present themes and 14 sub-themes affecting price can enable health system policy-makers of developing countries like Iran to make the best decisions through strategic purchasing of drugs by the main insurers in order to improve access and health in the country.